2017
DOI: 10.5815/ijisa.2017.09.08
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of I-PD Controller for DC Motor Speed Control System by Adaptive Tabu Search

Abstract: Abstract-One of the modified versions of the PID controller is the I-PD controller. It was proposed for eliminating the proportional and derivative kick appeared during set point change. In this paper, the optimal I-PD controller design for DC motor speed control system by the adaptive tabu search (ATS), one of the most efficient metaheuristic optimization techniques, is proposed. In a control system, DC motor is the principle and it is widely used because of the power from existing direct-current lighting pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…The key drawbacks of PID control, however, are the undesirable control action that contribute to significant high percent overshoot and longer settling time [17]. In order to reduce these undesirable control effects, the PID control structure has been modified by many researchers, resulting in the Integral-Derivative-Proportional (IDP) [17] and Integral-Proportional-Derivative (IPD) [18,[26][27][28] control structures, which are used in particular applications.…”
Section: Pid Controllermentioning
confidence: 99%
“…The key drawbacks of PID control, however, are the undesirable control action that contribute to significant high percent overshoot and longer settling time [17]. In order to reduce these undesirable control effects, the PID control structure has been modified by many researchers, resulting in the Integral-Derivative-Proportional (IDP) [17] and Integral-Proportional-Derivative (IPD) [18,[26][27][28] control structures, which are used in particular applications.…”
Section: Pid Controllermentioning
confidence: 99%
“…This Microcontroller receives the wireless signal through RF receiver from the robot receiving the part. The microcontroller gives the instruction to the motor driver depending on the specific bits of the receiving signal to move the robot Forward, Backward, Left or Right [12].…”
Section: Motor Drivermentioning
confidence: 99%
“…For such a system, it is better to have a model based on system identification or empirical modeling [9]. The PID controller is the most common control algorithm [10,11,12]. A survey has shown that 90% of control loops are PI and PID structures [13,14].…”
Section: Introductionmentioning
confidence: 99%